The genetic structure and its legal and social impact on our contemporary Islamic jurisprudence - Al-Jubouri, Khatam Muzhar Hamad Hassoun (Al-Adab Journal, 2021)
The research dealt with the genetic structure or the genetic fingerprint: that is, the identity of each particular individual, as it is a method characterized by accuracy to facilitate the task of forensic medicine to know and verify the personality to be known and to know its genetic characteristics by taking it from any cell of blood, saliva, semen, urine, or other Forensic medicine has an important role in this aspect, and with all the terrible scientific progress in all areas of the universe, mankind and life, but there was no contradiction between the words of God fixed in the Qur’an and the purified Sunnah and any established scientific rule and truth. Rather, the Qur’an touched upon a set of scientific facts discovered by modern science After a few years, he found it very accurate, both in terms of the stages of embryos and how they were created Or in the fields of the creation of the universe, its origin, its basic elements, and so on, and this indicates something that indicates the existence of the greatness of the Creator, the truthfulness of the Muhammadan message, its validity for every time and place, its comprehensiveness and its ability to survive and continue and keep pace with the times, regardless of development and progress. Therefore, the genetic structure in contemporary Islamic jurisprudence represents the major role in establishing or denying crimes and attributing it, as well as the areas of its uses, including those of unknown lineage and the foundling, preventing access to curse and in the case of low suspicion, the exchange of births in hospitals, and other matters of great importance in the folds of this research and not the informant as the meanings.